Lattice dynamics of Ge1−xSnx alloy nanowires. Issue 19 (5th May 2022) - Raha, Sreyan; Biswas, Subhajit; Doherty, Jessica; Mondal, Prasanna Kumar; Holmes, Justin D.; Singha, Achintya
Abstract : Alloying group IV semiconductors offers an effective way to engineer their electronic properties and lattice dynamics. Abstract : Alloying group IV semiconductors offers an effective way to engineer their electronic properties and lattice dynamics. The incorporation of Sn in Ge permits a transition from an indirect to a direct bandgap semiconductor. Here, by combining polarization, laser power-dependent and temperature-dependent micro-Raman spectroscopy we explore the full lattice dynamics of Ge1− x Sn x ( x = 0.01, 0.06 and 0.08) alloy nanowires. In the high Sn content samples ( x ≥ 0.06), a low-frequency tail and a high-frequency shoulder are observed which are associated with the F2g optical phonon mode of Ge (Ge–Ge mode). The new modes are assigned to the stretching of Ge–Ge bonds due to Sn-induced lattice relaxation and compression, respectively. The symmetry of the observed Raman modes has been studied by polarization-dependent Raman scattering. Nonlinear fitting of the laser power-dependent intensity of the high-frequency Ge–Ge mode in the Ge1− x Sn x alloy nanowires with x = 0.06 and 0.08 suggests the activation of a third-order stimulated Raman scattering process, due to the high intensity localized electric field surrounding the Sn clusters. Finally, from the temperature-dependent Raman study, we have estimated the isobaric Grüneisen parameters for all the observed modes.